1,7-Diaminoheptane - M. P. M. Marques, Universidade de Coimbra, Portugal (My University, 2002)
Inelastic Neutron Scattering spectrum of 1,7-Diaminoheptane, H₂N-(CH₂)n-NH₂, measured on the TOSCA instrument.
1,7,1 diaminoheptane
1,7,2 diaminoheptane
Keywords: TOSCA